The bridge : a novel - Kingsbury, Karen (New York : Howard Books, 2012)
Ryan Kelly spends plenty of time at The Bridge--the oldest bookstore in historic downtown Franklin, Tennessee-- remembering the times he and Molly Allen--who moved to Portland--once spent there, and now, with the bookstore in deep financial trouble, it will take a miracle to keep tragedy from unfolding.
Includes excerpt from The chance ([16] p.).
Keywords: Bookstores -- Fiction; Man-woman relationships -- Fiction; Franklin (Tenn.) -- Fiction; Christmas stories; Love stories; Christian fiction